1995
DOI: 10.1002/ijc.2910610315
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD44 expression by the epstein‐barr virus latent membrane protein LMP1 is associated with lymphoma dissemination

Abstract: Epstein-Barr Virus (EBV) is implicated in the pathogenesis of endemic Burkitt's lymphoma (BL), B-cell lymphomas occurring under immunosuppression, nasopharyngeal carcinoma and Hodgkin's disease. Two distinct patterns of latent EBV gene expression occur in EBV-associated lymphomas. BLs typically display expression of the nuclear antigen EBNAI only, whereas EBV-associated, non-Burkitt B-cell lymphomas express at least 9 latent viral genes (6 EBNAs and 3 latent membrane proteins), reminiscent of in vitro EBV-immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…To look for potential binding candidates for ezrin, we evaluated which membrane-anchored cell-adhesion molecule binds phosphorylated ezrin. LMP1 is reported to be associated with ICAM-1 and CD44 (Walter et al ., 1995; Park et al ., 2002). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To look for potential binding candidates for ezrin, we evaluated which membrane-anchored cell-adhesion molecule binds phosphorylated ezrin. LMP1 is reported to be associated with ICAM-1 and CD44 (Walter et al ., 1995; Park et al ., 2002). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, LMP1 expression results in the induction of cell surface molecules and the activation of signaling pathways that contribute to cell attachment, migration, and invasion (49)(50)(51). The molecular mechanisms driving many of these changes are still unclear, but transcriptional upregulation by LMP1 clearly contributes.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was independent of other pathologic factors, since factors such as lymph node metastasis and lymphatic invasion were not significantly different between EBVaGC and EBV-negative carcinomas (Table III). There have been several observations regarding CD44-expression in EBV-associated malignancies (Wang et al, 1990;Walter et al, 1995;Brooks et al, 1995). The EBV-encoded latent membrane protein-1, LMP1, has been shown to upregulate the standard form of CD44 expression when it is introduced into lymphoma cell lines, such as Daudi or Burkitt lymphoma cells (Wang et al, 1990;Walter et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several observations regarding CD44-expression in EBV-associated malignancies (Wang et al, 1990;Walter et al, 1995;Brooks et al, 1995). The EBV-encoded latent membrane protein-1, LMP1, has been shown to upregulate the standard form of CD44 expression when it is introduced into lymphoma cell lines, such as Daudi or Burkitt lymphoma cells (Wang et al, 1990;Walter et al, 1995). On the other hand, immunohistochemical evaluation of both LMP1 and CD44 variants in nasopharyngeal carcinoma tissues demonstrated that there was no correlation between the expression of the 2 molecules (Brooks et al, 1995).…”
Section: Discussionmentioning
confidence: 99%